Pemberdayaan Masyarakat Melalui Program Bank Sampah Makmur Sejati di Kecamatan Waru Kabupaten Sidoarjo - Muhammad Nidhom Ari Wijaya; Ertien Rining Nawangsari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Sidoarjo Regency is an area with a high population density of 1.95 million people, the large number of residents will automatically increase the amount of waste in the area. Based on this, Sidoarjo Regency is trying to reduce the amount of waste by managing waste through the Department of Cleanliness and Parks (DKP) in collaboration with the Environmental Agency (BLH) and realized with a management called Waste Bank. The purpose of this research is to find out how empowerment through the true prosperous waste bank program in Waru village, Sidoarjo Regency This research uses a qualitative approach. Data collection techniques in this study used triangulation techniques such as observation, interviews and documentation. The data analysis technique in this study uses the miles and huberman model which consists of data collection, data condensation, data presentation and data conclusions. This research produces interesting findings including: 1) The application of the concept of acceptable in community empowerment has been carried out well by the Makmur Sejati Waste Bank. 2) The application of the accountable concept in community empowerment has not been carried out optimally due to the absence of routine reports related to data every month provided to the community. 3) The application of the concept of profitable in community empowerment has gone well. Makmur Sejati Waste Bank acts as a programme that can provide economic benefits to the community through the exchange of waste into money by saving. 4) The application of the sustainable concept in community empowerment has been running but not too optimal. Makmur Sejati Waste Bank can indeed overcome all obstacles and problems faced independently. 5) The application of the replicable concept in community empowerment has gone well. The distribution of savings funds to the community is running smoothly so that the community can take their savings at any time.